Management of Rabies Prophylaxis for Potential Bat Exposures in a Level III Neonatal Intensive Care Unit. (19th December 2016) - Bailey, Ann L.; Quick, Rachel D.; Dixon, Joanne; Hauger, Sarmistha B.
Abstract : This report describes the unique challenges of managing potential exposure to bats in a neonatal intensive care unit. The outcome demonstrates that rabies post-exposure prophylaxis can be safely administered to preterm infants with evidence that preterm infants are able to develop adequate titers post vaccination. Infect Control Hosp Epidemiol 2017;38:483–485